ANALISIS PERBANDINGAN VOLUME PEKERJAAN KONSTRUKSI MENGGUNAKAN METODE BIM DAN KONVENSIONAL - Aryadi, Sekar Melanie Putri; Herzanita, Ayu (Construction and Material Journal, 2024)
A project is an activity in which implementation is limited by time and resources. Every project planning must pay attention to the effective and efficient value so that the project can run well and achieve maximum results and quality as planned. Technology is increasingly used including in the construction sector. The use of Building Information Modeling (BIM) technology is one of the technologies that is widely used to minimize the need for costs and work time and can integrate information about the project directly to the various parties involved. This research was conducted by planning using the 3D BIM concept to see the results of the application of technology on the upper structure work and comparing the results of the calculation of the cost of the upper structure work carried out using the BIM method and the conventional method on the Urban Signature Apartment - LRT City Ciracas, East Jakarta. The research method used involved collecting project data includes shop drawings and material specifications. Then, 3D modeling was carried out using Autodesk Revit software, and existing data was analyzed to determine the volume of work and the total cost incurred. From the calculations, it can be concluded that using 3D BIM technology with Autodesk Revit software shows 6.69% difference compared to conventional methods.